Compassion Fatigue and Emtional Labor Relationship - Sema Urnek; Aydan Yüceler (Association of Nurse Managers, 2023)
Aim: The aim of the study is to determine and evaluate the relationship between compassion fatigue And emotional Labor in nurses working in Meram Medical Faculty Hospital and Selcuk Medical Faculty Hospital. Method: The descriptive and correlational research was conducted with 493 nurses working at Meram Medical Faculty Hospital and Selcuk Medical Faculty Hospital. In the research, a questionnaire about personal and professional characteristics, 'Compassion Fatigue Scale-Short Form' and 'Emotional Labor' scale were used. Descriptive statistical analyzes were used to analyze the data. Results: It was determined that 66.3% of the nurses participating in the study were women, 62.9% had a bachelor's degree and 15.8% worked in internal services. Emotional labor scale total (2.11, SD=0.79) and compassion fatigue scale total score (2.41, SD=0.81) were found. It was concluded that there was a weak positive correlation between emotional labor and compassion fatigue (r= 0.325; p<0.01). Conclusion: According to the results of the research, it was determined that the nurses who exhibited emotional labor experienced compassion fatigue. In the light of these findings, it is important to take various measures to strengthen the spiritual feelings of the nurses in this group and to reduce the effects of compassion fatigue. In this context, emotional support can be provided by organizing appropriate seminars and conferences for nurses who exhibit emotional labor. Such measures can positively affect nurses' mental health and job performance. It is of great importance that nurses can strengthen their spiritual feelings in order to reduce work stress, prevent emotional fatigue and achieve better job satisfaction.